French presence and its impact on the emergence of Cambodian nationalism (1920-1937) - Oda, Dr. Hussein Abd Al Kadhum (Thi Qar Arts Journal, 2022)
This paper examines the French presence and its effect on the emergence of Cambodian nationalism (1920-1937). There were serious measures on the part of the French to change the general conditions in the Cambodian kingdom for the better, but because the French continued their repressive methods against the Cambodians that gave rise to nationalist feelings against them. The turmoil of political and economic conditions during the years (1927-1935) helped the emergence of the Hindu Communist Party during the year 1930 in Indochina. The establishment of the Nagravata newspaper and its impact on Cambodian society (1936-1937) was not against the French presence in Cambodia but on the contrary, the other Cambodian newspaper and publications were promoting that the Cambodians (Khmer) viewed the French as protectors against their neighbors, and that the main enemy was the Vietnamese, but at The establishment of the Cambodian Youth League began to demand Cambodian rights from French colonialism.